Effectiveness Corporate Social Responsibility Program in Distribution of Assistance Funds - Tiwi, Sirni Dia; Rossevelt, Franklin Asido (Jurnal Kebijakan Publik, 2025)
PTPN IV (Perkebunan Nusantara IV) is one of the companies that implements a Corporate Social Responsibility (CSR) program through the Partnership and Community Development Program (PKBL). In this study, the researcher focuses on the community development program of PTPN IV, specifically District II Berangir, which faces several obstacles such as a lack of socialization about the program, a rather complex program submission process, and funds received that do not match the funding requested in the proposal. This research aims to explain in detail the extent of the programs carried out by the District II Berangir Office, in order to assess the effectiveness of these programs on the communities surrounding the area. Practically, this research aims to provide contributions to PTPN IV as consideration in the implementation of CSR. The assessment indicators used by the researchers are based on Sutrisno's (2007) perspective, namely (1) understanding of the program, (2) targeting accuracy, (3) achievement of objectives, and (4) real change. This research employs a qualitative method with a descriptive approach. The results indicate that PTPN IV District II Berangir has effectively implemented the CSR program, as the programs implemented are running properly and in accordance with the needs of the community. However, there are still several challenges in its implementation, such as the complex process of applying for assistance, limited budget allocation which prevents reaching all target groups, and the company's limitations in monitoring the programs.